GARAP PERTUNJUKAN WAYANG WAHYU LAKON NABI ELLIA - Blacius Subono (Institut Seni Indonesia Surakarta, 2020)
This art work represents an activity of composing pakeliran (puppet show) script of Wayang Wahyu entitled Nabi Ellia. The activity includes script composing starting from vocabularies selection of catur, sabet, and iringan (accompaniment). This work aims to describe the story of Nabi Ellia into the vocabularies of pakeliran and to compose a pakeliran script entitled Nabi Ellia with the pattern of short pakeliran. Result of the activity includes: the description of pakeliran Wayang Wahyu vocabularies entitled Nabi Ellia; the script of Wayang Wahyu show entitled Nabi Ellia in short treatment; and the publication of the article in journal. This art work uses an approach adopted from theories of puppetry. The method used includes technique of library studies or content analysis, deep interview, focus group discussion (FGD), passive role observation, voice recording, audio visual recording, and photography. Based on the method and approach, the result produced is a complete script of Wayang Wahyu performance entitled Nabi Ellia.Keywords: script, Wayang Wahyu, Nabi Ellia.